2016
DOI: 10.1073/pnas.1615926113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electron count and chemical complexity in the Ta-Nb-Hf-Zr-Ti high-entropy alloy superconductor

Abstract: High-entropy alloys are made from random mixtures of principal elements on simple lattices, stabilized by a high mixing entropy. The recently discovered body-centered cubic (BCC) Ta-Nb-Hf-Zr-Ti highentropy alloy superconductor appears to display properties of both simple crystalline intermetallics and amorphous materials; e.g., it has a well-defined superconducting transition along with an exceptional robustness against disorder. Here we show that the valence electron count dependence of the superconducting tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 38 publications
8
110
0
Order By: Relevance
“…We also show that superconductivity in our alloys as well as that in crystalline HEAs [18,21,23] and binary transition metal alloys (e.g. [43]) is determined by their electronic structure and shows universal variation with the band (bare) density of states.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…We also show that superconductivity in our alloys as well as that in crystalline HEAs [18,21,23] and binary transition metal alloys (e.g. [43]) is determined by their electronic structure and shows universal variation with the band (bare) density of states.…”
Section: Introductionmentioning
confidence: 58%
“…These measurements have shown that the coefficient γ of the electronic contribution to LTSH, which is proportional to dressed DOS at E F , N γ (E F ) structural change obey the Dynes-Varma correlation [58] which seems valid for all disordered transition metal alloys, both crystalline (e.g., [21,23]) and amorphous [43]. As already noted in [24], since N γ (E F ) is enhanced by the electron-phonon interaction, it cannot be used to prove that the changes in figure 4 for x > 0.35 are due to change in N 0 (E F ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…It is a type-II superconductor with the transition temperature of T c = 7.3 K. Experimental data as well as theoretical calculations [10] suggest conventional mechanism of superconductivity with a relatively strong electron phonon coupling parameter λ ∼ 1. Several other examples of * wiendlocha@fis.agh.edu.pl superconducting HEAs were later reported [11][12][13], however, the TaNbHfZrTi family is still the most investigated one [9,10,14,15]. When the atomic concentration is slightly changed to Ta 33.5 Nb 33.5 Hf 11 Zr 11 Ti 11 [15] [denoted as (TaNb) 0.67 (HfZrTi) 0.33 or TNHZT in short], superconducting transition temperature slightly increases to 7.7 K. This alloy also hosts a cubic body-centered crystal structure, with the lattice parameter of 3.34Å.…”
Section: Introductionmentioning
confidence: 99%